Interaction potential of the multitargeted receptor tyrosine kinase inhibitor dovitinib with drug transporters and drug metabolising enzymes assessed in vitro - Weiß, Johanna; Theile, Dirk; Dvorak, Zdenek; Haefeli, Walter E. (Pharmaceutics, 2014)
Dovitinib (TKI-258) is under development for the treatment of diverse cancer entities. No published information on its pharmacokinetic drug interaction potential is available. Thus, we assessed its interaction with important drug metabolising enzymes and drug transporters and its efficacy in multidrug resistant cells in vitro.